Rare bird documentation form for Peregrine Falcon at Coralville Reservoir, 1982 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1982)
Rare bird documentation form for a Peregrine Falcon at Coralville Reservoir in Johnson County, IA on October 10, 1982. Epson - sheet feed